Dyes Degradation with Fe-Doped Titanium Nanotube Photocatalysts Prepared from Spend Steel Slag - Chih Ming Ma; Yu Jung Lin; Ren Wei Shiue; Chang Tang Chang (International Journal of Photoenergy)
TiO2 has been studied most commonly because it has high stability, nontoxicity, high catalytic activity, and high conductivity. Many studies have shown that TiO2 would generate electron-hole pairs illuminated with UV and surround more energy than that before being illuminated. In this study, the titanium nanotube (TNT) photocatalysts were prepared to increase the surface area and adsorption capacity. The Fe TNT was also prepared from a slag iron since many slag irons cause waste treatment problems. In this study, a different Fe loading was also assessed since TNT doped with metals can be used to improve the degradation efficiency. Furthermore, five kinds of dye concentration, including 10, 20, 100, 200, and 400 ppm, and five kinds of Fe-doped content, including 0, 0.77, 1.13, 2.24, and 4.50%, were tested. Different kinds of reaction time and dye species were also assessed. In this result, Direct Black 22 was the most difficult to be degraded, although the concentration was decreased or the dose amount was increased. The degradation efficiency of 10 ppm Direct Black 22 was below 40% with 0.04 gL−1 TNT under 365 nm UV irradiation.